Archpriest Gregory Prozorov (1864–1942), rector of the parish of Moscow Patriarchate in Berlin - Maxim Sorokin; Alexander Bertash (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article examines the biography of one of the significant figures of the Russian Orthodox Church of the twentieth century – Archpriest Grigory Yakovlevich Prozorov. After graduating from the Kiev Theological Academy, he was actively engaged in pedagogical and spiritual-educational, as well as socio-political activities, being an adherent of extreme right-wing views. In exile, in Serbia and since 1924 in Germany, Archpriest G. Prozorov remained under the jurisdiction of Metropolitan Evlogiy (Georgievsky), refusing to submit to Bishop Tikhon (Lyashchenko) of the ROCOR. Since 1930, he was the only representative of the Church of the Moscow Patriarchate in Germany, remaining faithful to it until the end of his life. The parishioners of the temples of Archpriest Gregory were famous scientists S. L. Frank and I. A. Stratonov. canonical and property, disagreements between the three branches of Russian Orthodoxy in Germany: ROCOR, "Evlogians" - supporters of Metropolitan Evlogy and the Moscow Patriarchate, on the other hand – in the face of harassment by German punitive authorities, in particular, the Gestapo. The article is based on numerous materials, first introduced into scientific circulation from the Bundesarchiv (Berlin), the Russian State Military Archive and Russian emigrant periodicals in Germany.